A Theoretical Framework for Studying Teachers' Curriculum Supplementation. (June 2022) - Silver, Daniel
The vast majority of U.S. teachers supplement their officially adopted curriculum materials with unofficial materials. Despite this, the body of supplementation-relevant literature tends not to focus on supplementation specifically, so lacks cohesion, and sometimes fails to capture all aspects the phenomenon. I systematically review supplementation-relevant literature from 2015 to 2020 and report seven areas of consensus in the literature around (1) who is involved in teacher-level curriculum supplementation, (2) important dimensions of supplementation, and (3) the educational value of supplementation. To provide future researchers a common starting point for studying teacher curriculum supplementation, I propose the Teacher Curriculum Supplementation Framework, a flexible yet testable analytical tool for systematizing scholarly inquiry around teacher curriculum supplementation and its effects on teachers and students.